Synthesis, antiproliferative activity and 2D-QSAR study of some 8-alkyl-2,4-bisbenzylidene-3-nortropinones - George, Riham F.; Wink, Michael (Future medicinal chemistry, 2018)
Aim: Colon cancer is the third leading cause of death worldwide; therefore, there is a need for an effective therapy with lower side effects. Methods: A series of 8-alkyl-2,4-bisbenzylidene-3-nortropinones 3 & 14-39 was prepared via Claisen-Schmidt condensation of 8-alkyl-3-nortropinones 11-13 with different aromatic aldehydes. The target compounds were screened for their antiproliferative activity. Results: Most of the prepared compounds showed promising antiproliferative activity against many of 60 National Cancer Institute cell lines at 10 μM. Furthermore, 8-ethyl-2,4-bis(3,4-dimethoxybenzylidene)-8-nortropin-3-one 29 and its 3,4,5-trimethoxy analog 30 were the most active compounds against HCT116 cell line with IC50 values 0.01 and 0.46 μM, respectively. Using CODESSA-Pro software, a significant 2D-quantitative structure-activity relationship (QSAR) model was obtained. Conclusion: The 8-Alkyl-2,4-bisbenzylidene-8-azabicyclo[3.2.1]octan-3-one represents an interesting core for further structural optimization to obtain more promising hits.
Gesehen am 16.12.2019